In Vitro Total Antioxidant and Antimicrobial Activities of Essential Oils from Leaves and Rind of Aegle marmelos L. Correa - Mehmood, Ferhat; Nadeem Asghar, Muhammad; Khan, Zaheer-ud-Din; Mehmood, Shahid; Zia, Iram (Asian Journal of Chemistry, 2011)
Aegle marmelos L. Correa is a pharmaceutically important plant which has been claimed to be effective against various diseases in the folk medicinal system of Indo-Pak subcontinent. A detailed study regarding total antioxidant capacity and radical scavenging and antimicrobial effects of the essential oils from leaves of Aegle marmelos L. Correa (AML) and Aegle marmelos L. rind (AMR) of this plant were investigated. Essential oils obtained from steam distillation process were subjected to 2,2'-azinobis(3-ethylbenzothiazoline-6-sulpohonic acid) (ABTS) radical cation decolorization, ferric reducing antioxidant power (FRAP), 2.2'-diphenyl-1-picrylhydrazil (DPPH) radical decolorization, total phenolic and total flavonoid contents, lipid peroxide inhibition using linoleic acid emulsion, superoxide anion radical scavenging and iron chelation activity assays. Total phenolic and total flavonoid contents values were found to be 18.078 and 13.310 mg/L gallic acid equivalent and 3.349 and 12.087 mg/L quercetin equivalent for AML and AMR, respectively. A linear correlation was observed between the per cent inhibition of ABTS radical cation and the amount of essential oils from leaves (R2 = 0.9973) and rind (R2 = 0.997). The per cent superoxide anion radical scavenging activity was found to be 47.37 and 2.50 for AML and AMR, respectively. The reducing power in terms of FRAP values were found to be 1.2 and 2.2 mM FeSO4 for AML and AMR, respectively. Both AML and AMR exhibited good metal chelating activities, 62.75 and 78.67 for AML and AMR, respectively. The oils also showed antimicrobial and antifungal activities comparable to chloramphanicol. The data obtained from oils demonstrate the powerful antioxidative, radical scavenging and antimicrobial properties of the plant.